2022
DOI: 10.1177/09544054221135388
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of sheet metal forming of an Al-Mg alloy incorporating plane strain properties in the yield criterion

Abstract: In this work, numerical simulation of AA5083-O aluminum alloy sheets is carried out using Yld2000-2d yield criterion to predict thinning and variation of load with displacement in sheet metal forming. It has been found that the accuracy of predictions in numerical simulation depends on the coefficients and the stress exponent used in the yield criterion. Hydraulic bulge tests with circular and elliptical die cavities are performed to characterize the material in equi-biaxial and plane strain conditions. An imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The results showed that increasing the maximum hydraulic pressure could effectively reduce the thinning of the critical zone. Prakash et al 22 used the Yld2000-2d yield criterion to simulate the AA5083-O aluminum alloy sheet numerically and predicted the thinning and load variation with displacement during the sheet forming process. Hydraulic bulge tests with circular and elliptical die cavities are performed to characterize the material in equi-biaxial and plane strain conditions.…”
Section: Optimization Of the Loading Path Of The Hydraulic Pressurementioning
confidence: 99%
“…The results showed that increasing the maximum hydraulic pressure could effectively reduce the thinning of the critical zone. Prakash et al 22 used the Yld2000-2d yield criterion to simulate the AA5083-O aluminum alloy sheet numerically and predicted the thinning and load variation with displacement during the sheet forming process. Hydraulic bulge tests with circular and elliptical die cavities are performed to characterize the material in equi-biaxial and plane strain conditions.…”
Section: Optimization Of the Loading Path Of The Hydraulic Pressurementioning
confidence: 99%
“…[1][2][3][4] With the continuous development and maturity of finite element simulation technology, more and more scholars today were using finite element analysis to study the deformation process of sheets. 5,6 Finite element simulation also plays an important role in the study of part springback. Sun et al 7 found that the hot forming of high-strength steel significantly reduced springback by about 62% compared to cold forming through the finite element model developed and also found that rapid forming was beneficial in reducing springback.…”
Section: Introductionmentioning
confidence: 99%